Hubungan Return SRELATIONSHIP OF INDONESIA & U.S AGGREGATE STOCK RETURNS PRE AND POST GLOBAL FINANCIAL CRISIS (GFC)aham Agregat Indonesia & AS Sebelum dan Setelah Krisis Keuangan Global (GFC) - Roby Arlan; Ahmad Danu Prasetyo; Adelia Putri Pratiwi; Reza Erlangga Ludwian (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This article studies the correlation and volatilities between Indonesia's stock price (JKSE) and U.S's stock price (DJI, NASDAQ) aggregate return before and after The U.S. Subprime Mortgage Crisis in 2008. We use VAR Model to study the correlation and DIAGONAL GARCH-BEKK Model to see the volatilities between the two stock markets. We found that Indonesia's aggregate return is slightly more affected by its own past conditional volatilities after the crisis, contrary to the U.S aggregate return, which is somewhat less impacted by its own past conditional volatilities in the period after the crisis. This study will contribute to literature regarding the complex relationship between aggregate stock market returns of Indonesia and the U.S. before the global financial crisis and the period after the global financial crisis to see how each country's aggregate stock market return influenced each other.